DINAMIKA ARUS DALAM MENDUKUNG PERIKANAN BUDIDAYA LAUT DI TELUK BONE - S. Pranowo, Widodo; D. Puspita, Candra; Bramawanto, Rikha; A. Adi, Rizky; Kusumawardani, Anastasia R. T. D. (Jurnal Harpodon Borneo, 2014)
Ocean current condition which is hypothized support potential fisheries in Teluk Bone is interesting to be studied. This article presents the result of a simulation of the three-dimensional hydrodynamics modeling, in order to understand the current circulation in Teluk Bone. Snapshots of the modeling produce the phenomena that occur in Southeast Monsun period (August 1-10, 2004) in order to match with data verification available. Sea surface elevation at spring tide is 0.0492 – 2.4140 meters. The speed velocity of surface current at same condition in range of 0.5x10-3 – 12.25x10-3 m/sec, with dominant direction alongshore of the east coast and then headed North and West. Downwelling occurs somewhere in west coast and upwelling occurs somewher in east coast. The vertical upwelling velocity is in range of 0,5x10-3 - 3,5x10-3 m/sec, while vertical downwelling velocity is in range of 0,5x10-3 - 4,6x10-3 m/sec. In this monsoon period, the velocity of surface current support of the marine aquaculture activities, since the range is still follow to UNDP/FAO standard values of <100 cm/sec. The low vertical velocity of upwelling and downwelling keeps nutrients in a low mixing condition, then those can be stable utilized by phytoplankton. Palopo, Suli and Muranti are the coastal city location nearby that upwelling and downwelling occurs and sea surface current velocity in good suitability for seaweed cultivation, fish farming on “keramba” floating cages/nets and some oyster pearl cultivation. Keywords : current pattern, hydrodynamics modeling, Teluk Bone, marine aquaculture